2011
DOI: 10.1093/toxsci/kfr020
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Dibutyl Phthalate Fetal Testis Endocrine Disruption Correlates with Inhibition of SREBP2-Dependent Gene Expression Pathways

Abstract: Fetal rat phthalate exposure produces a spectrum of male reproductive tract malformations downstream of reduced Leydig cell testosterone production, but the molecular mechanism of phthalate perturbation of Leydig cell function is not well understood. By bioinformatically examining fetal testis expression microarray data sets from susceptible (rat) and resistant (mouse) species after dibutyl phthalate (DBP) exposure, we identified decreased expression of several metabolic pathways in both species. However, lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Testosterone gets produced by steroidogenesis enzymes/associated proteins located in the LC mitochondrion (Mt) and smooth endoplasmic reticulum (sER). LC viability and testosterone production are critical during fetal development for male sexual differentiation, and postnatally for initiation and maintenance of spermatogenesis, and expression of male secondary sex characteristics (Johnson et al, 2011(Johnson et al, , 2012. Recently we reported, following prenatal DBP oral exposure to rats, a significant LC-sER decrease in postpuberty rats , but the detailed morphological alterations of LC-Mt remained ambiguous.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Testosterone gets produced by steroidogenesis enzymes/associated proteins located in the LC mitochondrion (Mt) and smooth endoplasmic reticulum (sER). LC viability and testosterone production are critical during fetal development for male sexual differentiation, and postnatally for initiation and maintenance of spermatogenesis, and expression of male secondary sex characteristics (Johnson et al, 2011(Johnson et al, , 2012. Recently we reported, following prenatal DBP oral exposure to rats, a significant LC-sER decrease in postpuberty rats , but the detailed morphological alterations of LC-Mt remained ambiguous.…”
Section: Introductionmentioning
confidence: 98%
“…As a function of the alcohol chain length, they may be separated into two distinct groups: i) low molecular-weight phthalates containing three to six carbons in the ester functionality, and ii) high molecular-weight phthalates that contain greater than six carbons in the ester functionality (Blount et al, 2000;Barlow and Foster, 2003;Barlow et al, 2004). Phthalates are used to impact product flexibility, durability, transparency, and longevity; and are present in many common products; children's toys, cosmetics, detergents, electronics, food packaging, paints, personal care products, pharmaceuticals, and waxes (Wolf et al, 1999;OSHA, 2009;Hannas et al, 2011;Johnson et al, 2011Johnson et al, , 2012Guo et al, 2013). The fact that phthalates are present in many products means that their inherent human exposures and health-risk assessments are a concern.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mode of action of DEHP in mice seems to be different from that in rats. Several studies found that mouse testosterone production was unaffected by phthalate exposure (Johnson et al, 2011;van den Driesche et al, 2012). However, some researchers found that the reproductive disorder of fetal mouse were induced by in utero phthalate exposure, including induced multinucleated germ cells (MNGs), increased seminiferous cord diameters, and altered expression of thousands of fetal testis genes (Gaido et al, 2007;Johnson et al, 2011;Lehraiki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that mouse testosterone production was unaffected by phthalate exposure (Johnson et al, 2011;van den Driesche et al, 2012). However, some researchers found that the reproductive disorder of fetal mouse were induced by in utero phthalate exposure, including induced multinucleated germ cells (MNGs), increased seminiferous cord diameters, and altered expression of thousands of fetal testis genes (Gaido et al, 2007;Johnson et al, 2011;Lehraiki et al, 2009). A recent study found that dipentyl phthalate (DPeP) significantly reduced testosterone production by 25-30% at a dose level that did not induce any maternal or fetal toxicity in mice, but the 50% effective dose for this effect was about fourfold higher than in the rat (Furr et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…c and d Same at higher magnification showing degeneration and loss of germ cells and Sertoli cells with evident granulation and vacuolization of the cytoplasm as well as degeneration of Leydig cells. H&E ×1,in Leydig cells(Johnson et al 2011) with PPARα probably acting as an indirect transrepressor of steroidogenic factor 1 (SF1) on steroidogenic genes(Plummer et al 2013). However,Hu et al (2013) reported that the lowdose MBP-a metabolite of DBP enhanced SF1 regulation on steroidogenic acute regulatory protein (StAR) which although is modulated by numerous transcription factors induced steroidogenesis whileNair et al (2008) observed decline in serum testosterone production.…”
mentioning
confidence: 99%